Challenges for safety intervention in emergency vehicle fleets: A case study. (March 2020) - Muir, Carlyn; Newnam, Sharon; Newstead, Stuart; Boustras, George
Highlights: Emergency vehicle drivers are at risk on the road. Challenges for safety intervention are unique and occur across the system. Emergency vehicle safety intervention needs to be holistic. Abstract: The emergency services play an integral role in public health and safety, and operating motor vehicles represents a key activity for these staff. Emergency service workforces are large, and under ever increasing demands. Motor vehicle crashes involving emergency vehicles have been recognized as a serious problem, with emergency and high-risk operating environments routine for these workers. However, given the unique operational structures of these organizations, implementing effective interventions can be difficult. A case study was undertaken with a large emergency service organization in Australia. A mixed methods approach to data collection was used to address the primary aim of exploring the challenges, barriers and facilitators for the uptake of fleet safety initiatives in the emergency service organization. Case study data were collected through document analysis, interviews, observations and site visits. This paper identifies a number of challenges associated with implementing effective interventions in emergency service fleets. Despite knowledge of the specific attributes and risk factors of workplace driving, prevention strategies have traditionally been informed by more general road safety approaches and are driver-centric, which is a similar observation for emergency fleets. Factors contributing to risk, as well as challenges in adhering to safe working practices, were identified across all levels of the risk management framework, particularly at the Agency level (training; management of drivers, including volunteers; fleet purchasing decisions), Regulator level (auditing) and Government level (allocation of resources; response time targets; road rules).